This is it ! : Indicating and looking in collaborative work at distance - Mauro Cherubini; Marc-Antoine Nüssli; Pierre Dillenbourg (Bern Open Publishing, 2010)
Little is known of the interplay between deixis and eye movements in remote collaboration. This paper presents quantitative results from an experiment where participant pairs had to collaborate at a distance using chat tools that differed in the way messages could be enriched with spatial information from the map in the shared workspace. We studied how the availability of what we defined as an Explicit Referencing mechanism (ER) affected the coordination of the eye movements of the participants. The manipulation of the availability of ER did not produce any significant difference on the gaze coupling. However, we found a primary relation between the pairs recurrence of eye movements and their task performance. Implications for design are discussed.